The Transformation of Islamic Political Identity in The Countryside of Banyuwangi Through Osing Culture in 1970-2005 - Muhammad Agung Pramono Putro; Nur Aini Setiawati (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This research examines why local identity building was conducted in Osing village, Banyuwangi Regency, East Java, and how this identity was initiated and invested by actors who have power using Islamic political identity. To respond to these questions, this research used the historical method by utilizing primary and secondary sources, such as official archive in form of decrees, interview with historical actors, and various references such as books, journals, and newspapers. This research findings are the following: Osing’s identity was a deliberate blueprint and not a natural continuity. This construction involved cultural practitioners, journalists, artists, intellectuals, traditional figures, and national administrators. Osing’s identity construction, transformation, negotiation, and mobility are the site of the contention of various interest. The attempt of creating a sympathetic and caring reputation of Osing culture represented by almost all of Banyuwangi regent continued from the New Order era until the post-Reformation era, despite various paradigm shifts. This needs to be interpreted as efforts to build identity and not just to eliminate the stigma attached. It has had an impact on political support and legitimacy in Banyuwangi, especially Osing Kemiren Village.